A Simulative and Experimental Approach for the Design and Optimization of Atmospheric Pressure Low Power RF Thermal Plasma Processes. Issue 4 (20th December 2016) - Traldi, Enrico; Boselli, Marco; Gherardi, Matteo; Colombo, Vittorio
Abstract : Based on the comparison of simulative and experimental data, an approach is presented for the design and optimization of processes assisted by low power atmospheric pressure Radio Frequency (RF) thermal plasmas. High Speed Imaging (HSI), Schlieren Imaging (SI), and temperature measurement on the surface of the substrate are performed to characterize the effect of the interaction of the RF torch effluent with a substrate placed downstream of the torch outlet. The related processes are simulated in 2‐D axisymmetric and 3‐D domains for different operating conditions, for the plasma generation region and for the downstream region, respectively. The comparison of numerical and experimental results is used to in depth characterize and investigate the behavior of the effluent of the RF torch. Abstract : A simulative and experimental approach for the design of processes assisted by atmospheric pressure low power Radio Frequency thermal plasma is presented. A comparison is made between data obtained from diagnostic techniques and simulations in order to characterize the behavior of the effluent of the plasma torch for different operating conditions in a free flow regime or impinging on a substrate.